Protocol for a randomised, double-blind, placebo-controlled study of grass allergen immunotherapy tablet for seasonal allergic rhinitis: time course of nasal, cutaneous and immunological outcomes. Issue 1 (December 2015) - Steveling, Esther; Lao-Araya, Mongkol; Koulias, Christopher; Scadding, Guy; Eifan, Aarif; James, Louisa; Dumitru, Alina; Penagos, Martin; Calderón, Moisés; Andersen, Peter; Shamji, Mohamed; Durham, Stephen
Abstract Background Seasonal Allergic Rhinitis is characterised by inflammation of the nasal mucosa upon exposure to common aeroallergens, affecting up to 20–25 % of the population. For those patients whose symptoms are not controlled by standard medical treatment, allergen specific immunotherapy is a therapeutic alternative. Although several studies have shown changes in immunologic responses as well as long term tolerance following treatment with a sublingual allergy immunotherapy tablet, a detailed time course of the early mechanistic changes of local and systemic T and B cell responses and the effects on B cell repertoire in the nasal mucosa have not been fully examined. Methods/design This is a randomized, double-blind, single-centre, placebo controlled, two arm time course study based in the United Kingdom comparing sublingual allergy immunotherapy tablet (GRAZAX®, ALK-Abello Horsholm, Denmark) plus standard treatment with placebo plus standard treatment. Up to 50 moderate to severe grass pollen allergic participants will be enrolled to ensure randomisation of at least 44. Further, we shall enrol 20 non-atopic volunteers. Screening will be completed before eligible atopic participants are randomised to one of the two treatment arms in a 1 to 1 ratio. The primary endpoint will be the total nasal symptom score assessed over 60 min following grass pollen nasal allergen challenge after 12 months of treatment. Clinical assessments and/or mechanistic analyses on blood, nasal fluid, brushing and biopsies will be performed at baseline at 1, 2, 3, 4 (coinciding with the peak pollen season), 6 and 12 months of treatment. After 12 months of treatment, unblinding will take place. Those atopic participants receiving active treatment will continue therapy for another 12 months followed by a post treatment phase of 12 months. Assessments and collection of biologic samples from these participants will take place again at 24 and at 36 months from the start of treatment. The 20 healthy, non-atopic controls will undergo screening and one visit only coinciding with the 12 month visit for the atopic participants. Discussion The trial will end in April 2017. The trial is registered with ClinicalTrials.gov and the trial identifying number is NCT02005627. Trial registration: Primary Registry: ClinicalTrials.gov, Trial Identifying number: NCT02005627, Secondary identifying numbers: EudraCT number: 2013-003732-72 REC: 13/EM/0351, Imperial College London (Sponsor): 13IC0847, Protocol Version 6.0, Date: 16.05.2014